The impact of parenting styles on depression among high-risk adolescents of different genders in chinese urban samples: the mediating effects of adverse childhood experiences and learning burnout - Tang, Peiqi; Guo, Yuxuan; Xiao, Xiaoqiang; Li, Juexi; Pu, Ting; Yang, Ting; Zuo, Haixi; Fan, Xiaoxia; Li, Liyuan; Zhou, Bo (Frontiers in Psychiatry, 2025)
BackgroundParenting styles, adverse childhood experiences, and learning burnout are significant risk factors for depression in adolescents; however, the underlying mechanisms and gender differences remain inadequately explored. This study aims to investigate the mediating roles of adverse childhood experiences and learning burnout in the relationship between parenting styles and adolescent depression, as well as to examine potential gender differences.MethodsA total of 3,180 high-risk adolescents participated in this study. Key variables were assessed using standardized instruments, including the Short Egna Minnen av Barndom Uppfostran (s-EMBU), the Childhood Trauma Questionnaire-Short Form (CTQ-SF), the Learning Burnout Scale, and the Patient Health Questionnaire-9 (PHQ-9). Structural equation modeling analysis was performed using AMOS 24.0.ResultsAdverse childhood experiences (β = 0.305, 95% CI [0.203, 0.420]) and learning burnout (β = 0.118, 95% CI [0.064, 0.183]) emerged as mediators between various parenting styles and depression. Among female adolescents, parenting styles influenced the onset of depression through both direct and sequential mediation involving adverse childhood experiences and learning burnout. Conversely, among male adolescents, overprotective parenting styles impacted depression through the mediating effect of learning burnout.ConclusionAdverse childhood experiences and learning burnout mediate the relationship between different parenting styles and depression. Additionally, the pathways through which parenting styles affect depression demonstrate gender differences.